Natural thermal plasters for fibre-composite matrices. Structural-energy-environmental analysis - Rosa Romano; Valerio Alecci; Antonino Maria Marra; Elisabetta Palumbo (Agathón)
The article presents the first results of MIRACLE research, aimed at designing, testing, and implementing innovative reinforcement systems with bio-composite matrix, with additives containing natural thermal-plasters, usable in the restoration of residential buildings created before 1945. Starting from a brief description of the properties of fibre-reinforced cement organic matrices, supported by a survey of international research aimed at developing innovative methodologies, systems, and components used to improve the energy and mechanical performances of listed historic buildings, the most suitable thermal-plasters will be analysed (among those existing on the Italian market), identifying the performance characteristics both in terms of mechanic and thermal and environmental sustainability.